Antifungal activity of Cassia fistula Linn. against some pathogenic fungi - Ishfaq Rashid War,; Showkat Ahmad Ganie,; Rajneesh Kumar Agnihotri,; Bhavna Sharma,; Surabhi Mahajan,; Rajendra Sharma, (International Journal of Phytomedicine, 2014)
Antifungal activity of number of phytochemicals has been reported. In the present study, aqueous and methanolic leaf extracts of Cassia fistula has been investigated for antifungal activity against some pathogenic fungal strains viz. Candida albicans, Microsporum gypseum and Aspergillus niger using the standard disc diffusion method. Methanolic extract had shown the maximum activity (13mm) against A. niger. Extracts showed a concentration dependent antifungal activity, with higher concentrations of 100 and 200 mg/ml showing greater zones of inhibition than with lower concentrations. The Minimum Inhibitory Concentration (MIC) ranged from 0.78 to 3.12 mg/ml. The in vitro findings justify the use of Cassia fistula in traditional medicine practice for the treatment of some fungal infections. However, study on the toxicity of the crude extracts and the compounds isolated from this plant should be assessed to ensure their eligibility to be used as sources of modern medicines.